Network modelling and prediction of retrograde gas behaviour in natural gas pipeline systems. (2016) - Jin, Tianying; H., Luis F. Ayala; Ityokumbul, M. Thaddeus
As retrograde gases are transported through pipeline systems, retrograde condensation may occur. The presence of this additional liquid phase is responsible for additional pressure losses in natural gas surface production systems. Gases and liquids have markedly different routing behaviour when moving concurrently through a network system and the determination of their distribution within the network is of vital importance for retrograde gas surface transportation operations. This study is aimed at developing and testing an analytical tool that predicts phase behaviour of retrograde gas in natural gas pipeline systems. This tool will allow operators to make better decisions regarding liquid phase removal from the network, pressure loss mitigation, design and location of surface production and separation equipment with an accurate map of the pressure, phase distribution and phase property inside the network. The proposed network model for retrograde gas is able to handle realistic field situations and allows the user to effectively track liquid and gas preferential routing within the network and provide guidance for improving the performance of the entire gas pipeline system.